Protein Phosphorylation in Human Health and Diseases - ถาวรพันธ์ , พงศกร; ธนาพงษ์ภิชาติ, สุภิญญา; บุญเชิด, หาญศึก (KKU Science Journal, 2019)
Protein phosphorylation-dephosphorylation is the common post-translational modifications that regulate the structures and functions of cellular proteins involved in diverse biological processes ranging from control of cellular fate to regulation of metabolism. Owing to its significant roles, the cell needs to tightly modulate the phosphorylation-dephosphorylation to sustain cellular integrity. Disruption or dysregulation of the phosphorylation-dephosphorylation could lead to diseases such as diabetes mellitus, Parkinsonism, Alzheimer’s disease and cancer. The review in this issue focuses on the significant role of protein phosphorylation-dephosphorylation and signaling mechanisms involved in the processes. This issue also provides the information of phosphorylation-related diseases, highlighting the application of phosphorylation in development of targeted therapy.